Consumer Based Competitive Priorities of Via Tuban Shrimp Paste in the Indonesian Market: An Importance Performance Analysis: Prioritas Kompetitif Berbasis Konsumen dari Terasi Udang Via Tuban di Pasar Indonesia: Analisis Kepentingan-Kinerja - Mahmudah Enny Widyaningrum; Andre Ridho Saputro; Eka Saputra; Diana Evawati; Muslichah Erma Widiana; Yoga Adi Prayogi (Universitas Muhammadiyah Sidoarjo, 2026)
This study evaluates the consumer-based competitive priorities of Via Tuban shrimp paste (terasi) by analyzing the gap between perceived importance and performance of key product attributes using Importance–Performance Analysis (IPA). Drawing on the resource-based view and consumer value theory, the research assesses seven attributes; quality, packaging, price, distribution, brand image, food safety, and promotion & innovation through a structured 5-point Likert survey administered to 65 purposively selected consumers. Findings reveal a significant shortfall in performance relative to expectations, with a grand mean importance of 4.26 and performance of 2.63. All attributes show negative gaps;